Answer:
![C=(17)/(7), D=-(4)/(7)](https://img.qammunity.org/2020/formulas/physics/middle-school/bwl6f9hipoc38q5rau5e60zgj12zwpbq74.png)
Step-by-step explanation:
The system of equation is the following:
![3C+4D=5\\2C+5D=2](https://img.qammunity.org/2020/formulas/physics/middle-school/llpira0n079j4v416tvx0to8qjoq98jqo6.png)
We can solve the system by expliciting C from the second equation. We get:
![2C+5D=2\\2C=2-5D\\C=(2-5D)/(2)=1-(5)/(2)D](https://img.qammunity.org/2020/formulas/physics/middle-school/r8a106kel5wsocwjau3lfx26z1j0337bif.png)
And if we know substitute C into the first equation, we find
![3C+4D=5\\3(1-(5)/(2)D)+4D=5\\3-(15)/(2)D+4D=5\\3-(15)/(2)D+(8)/(2)D=5\\3-(7)/(2)D=5\\-(7)/(2)D=2\\-7D=4\\D=-(4)/(7)](https://img.qammunity.org/2020/formulas/physics/middle-school/3u1ckzocxlreiw7u55tgpkxw2u3ffm5b2r.png)
And by substituting D into the second equation, we find
![C=1-(5)/(2)D=1-(5)/(2)(-(4)/(7))=1+(10)/(7)\\C=(7)/(7)+(10)/(7)=(17)/(7)](https://img.qammunity.org/2020/formulas/physics/middle-school/v41orhyppw20qsvl4r13h4taggsrawonf1.png)